Crystal structure of 3-(2-ethoxy-2-oxoethyl)-1-ethyl-1H-imidazol-3-ium hexafluoridophos-phate(V), C9H15F6N2O2P - Yuan Kun; Xiong Wan-Ming; Nie Xu-Liang; Peng Da-Yong; Chen Jing (Zeitschrift für Kristallographie - New Crystal Structures)
C9H15F6N2O2P, monoclinic, P21/n (no. 14), a = 8.3781(15) Å, b = 13.970(3) Å, c = 12.904(2) Å, β = 104.500(2)°, V = 1462.3(5) Å3, Z = 4, R gt(F) = 0.0677, wR ref(F 2) = 0.1977, T = 296(2) K.